Citra Perempuan dalam Kumpulan Cerpen Perempuan karya Mochtar Lubis Sebagai Alternatif Bahan Ajar Cerita Pendek di SMA - Sumarni, Sumarni; Wardianto, Bayu Suta; Kurniawan, Heru; Fadilah, Nurmilah (Balai Bahasa Provinsi Papua, 2022)
Women and literary works are inseparable unity. This is where the study of feminism in literary works oriented towards the state of women in literature was born. This study describes aspects of women's image contained in the group of women's short stories by Mochtar Lubis. The method applied to this study is qualitatively decisriptive. Data in research is analyzed by applying content analysis techniques, data collection processes applying library techniques, reading techniques, and recording techniques. The results and findings of the study are four forms of female imagery, namely: (1) physical image, (2) psychic image, (3) family image, and (4) community image. In addition, Mochtar Lubis's women's short story collection book can also be used as an alternative teaching material in short story learning which in the revised edition of the 2013 curriculum is contained in K.D. 3.8 about identifying the value of life contained in short stories and K.D. 3.9 about analyzing elements of short story builders by making the short story collection book as an increase in the wealth of short stories used in learning.